A comparative study of the application of systems thinking in achieving organizational effectiveness in Malaysian and Pakistani banks. Issue 4 (August 2018) - Akhtar, Ch. Shoaib; Awan, Sajid Hussain; Naveed, Shaheryar; Ismail, Kamariah
Highlights: Comparative study of banking industry of Pakistan and Malaysia. Systems thinking capability is crucial for organizational effectiveness. Understanding mental models is found insignificant in both countries. Continuous learning is highly significant in Pakistani banking industry. Dynamic thinking is highly significant in Malaysian banking industry. Abstract: The present work is a comparative study of the banking industry of Malaysia and Pakistan. The paper aims to measure the impact of individual systems thinking on the overall organizational effectiveness. Skilled individuals are considered as an asset of the organization especially when these individuals exhibit systems thinking capabilities that helps in achieving effectiveness. The sample consisted of 368 respondents belonging to lower and middle tier levels in the banking sector of both countries. The results indicate that Malaysian banking employees are ahead of their counterparts in Pakistan while applying systems thinking. The study is significant in enhancing the understanding of the importance of systems thinking for organizational effectiveness. The study has managerial implications for the top management of banks.